Anesthesia Workspace Cleanliness and Safety: Implementation of a Novel Syringe Bracket Using 3D Printing Techniques. (1st July 2019) - Long, Dustin R.; Doney, Allison; Bartels, Devan L.; Tan, Crystal E.; Sayal, Puneet K.; Anderson, Thomas A.; Agarwala, Aalok V.
Abstract : Purpose . Wide variability persists in the preparation and storage of common anesthetic medications despite the recognition of anesthesia workspace standardization as a national quality improvement priority. Syringe contamination and medication swaps continue to pose significant hazards to patient safety. Methods . We assessed differences in practice related to the availability of commonly prepared anesthetic medications. Using baseline provider surveys ( n  = 87) and anesthesia workspace audits ( n  = 80), we designed a custom syringe organization device using 3D printing techniques to serve as a cognitive aid and organizational tool. We iteratively tested and then deployed this device in all 60 operating rooms at a single institution, and then, repeated postintervention surveys ( n  = 79) and workspace audits ( n  = 75) one year after introduction. Results . Implementation was associated with significant improvements in provider-reported medication availability during coverage and handoff situations (43.7% versus 76.2% reporting 95% confidence preintervention versus postintervention, p < 0.001 ). This was substantiated by audits of the anesthesia workspace which demonstrated reduced variability in the location (p < 0.001 ) and availability (p < 0.001 ) of key medications. Provider confidence in the cleanliness of syringes was also improved (p = 0.01 ). A high degree of acceptance and compliance with the intervention was reported, with 80.4% of syringes observed to be stored in the device one year after implementation and approximately 95% of respondents reporting positive measures of usability and convenience. Conclusion . Use of a simple organizational device for syringes in the anesthesia workspace has numerous safety benefits. 3D printing offers improvements in adaptability and affordability compared with prior approaches.